Sistem Perbankan Islam di Indonesia: Sejarah dan Prospek Pengembangan - Suryani Suryani (IAIN Salatiga, 2012)
Islamic banking or sharia banking is a new phenomenon in the modern worldeconomy, its emergence as the intense efforts made by Islamic scholars in the development of Islamic economics in which it will be able to replace theconventional economic system based on the interest to the interest-freesystem. That’s why sharia banking system apply an interest-free system inoperation. Therefore, the closest term to define sharia banking is a bank that operates based on Islamic sharia principles, by reference to the Al-Quran and Sunnah as the basis or the legal and operational basis. Islamic banks were originally developed from the response of some economists and practitioners of Islamic banking that seek to accommodate pressure from various parties who want to make available services of the financial transactions carried out in line with moral values and principles of Islamic sharia. On his journey, sharia-based banking system is increasingly popular not only in Islamic countries but also western countries, characterized by increasingly the number of banks that implement this concept